2009
DOI: 10.1029/2008rs004079
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous radio interferometer and optical observations of ionospheric structure at the Very Large Array

Abstract: [1] Radio astronomers are searching the cosmos for new scientific discoveries at increasingly lower radio frequencies and with larger antenna arrays, but their observations of the sky are blurred by the dynamic ionosphere. At the same time, ionospheric scientists are seeking to understand, at increasingly higher spatial and temporal resolutions, the dynamics that drive the ionosphere and its effects on technological systems. Advancements in radio astronomy at the Very Large Array (VLA) are leading to advanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Observations of ionospheric disturbances with the VLA and a colocated all‐sky optical imager have also demonstrated that this extreme δ TEC precision makes the VLA uniquely sensitive to fine‐scale structure. During this campaign, the same disturbances observed with the optical imager were also detected with the VLA, but the VLA data also showed evidence of density fluctuations on much finer spatial and temporal scales that were absent within the airglow images (Coker et al, ).…”
Section: Introductionsupporting
confidence: 65%
“…Observations of ionospheric disturbances with the VLA and a colocated all‐sky optical imager have also demonstrated that this extreme δ TEC precision makes the VLA uniquely sensitive to fine‐scale structure. During this campaign, the same disturbances observed with the optical imager were also detected with the VLA, but the VLA data also showed evidence of density fluctuations on much finer spatial and temporal scales that were absent within the airglow images (Coker et al, ).…”
Section: Introductionsupporting
confidence: 65%
“…Other satellite-based remote-sensing platforms, including COSMIC, DMSP, and JASON, will also be available during overflights to provide further information about background ionospheric plasma and electrodynamic conditions in the ionosphere. A similar approach has been followed previously in the Combined Radio Interferometry and COSMIC Experiment in Tomography (CRICKET) campaign utilising the VLA (Dymond et al 2008;Coker et al 2009). This mix…”
Section: Ionospheric Scintillationmentioning
confidence: 99%
“…Many radio interferometer studies of the ionosphere have involved tracking a single bright source and measuring the phase fluctuations on each baseline (where a baseline refers to a pair of interferometric receivers) as a function of time [ Hamaker , ; Jacobson and Erickson , ; Coker et al , ; Helmboldt et al , , ]. The ionospheric phase ϕ ( Δθ) is proportional to the difference in TEC between the lines of sight to the two receivers, so this can be used to probe temporal variations in the differential TEC on spatial scales corresponding to the projection of the array onto the ionosphere.…”
Section: Introductionmentioning
confidence: 99%